1995
DOI: 10.1246/bcsj.68.1947
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanisms of Photoinduced Reduction of Methylviologen by N-Alkyltetraphenylporphyrinatozinc(II) in Methanol

Abstract: N-3-Bromopropyl-5,10,15,20-tetraphenylporphyrinato(1-)chlorozinc(II), [Zn(BrPrtpp)Cl], catalyzed the formation of a methylviologen radical cation (MV+•) on steady-state irradiation of degassed methanol solutions with visible light (>420 nm) in the presence of triethanolamine (TEOA). The initial rate (Vi) of the formation of MV+• was of first order in the concentration of MV2+ and in the intensity of light and was independent of the concentration of TEOA above 0.025 M. Plots of Vi vs. the concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…We have shown that the excited triplet state of 1Zn or 2Zn was intermolecularly quenched by free methyl viologen, similar to non- N- substituted Zn(II) porphyrins. In the case of the Zn(II) diad 10Zn , transient nanosecond-laser spectroscopy showed that no radical−ion intermediate was detected (Figure ) and the lifetime of the excited triplet state of 10Zn ( 3 ( 10Zn ) * ) became shorter than that of 1Zn : τ t = 3.0 μs ( 10Zn ) and τ 0 t = 7.9 μs ( 1Zn ) in MeCN and τ t = 3.5 μs ( 10Zn ) and τ 0 t = 4.4 μs ( 1Zn ) in MeOH.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…We have shown that the excited triplet state of 1Zn or 2Zn was intermolecularly quenched by free methyl viologen, similar to non- N- substituted Zn(II) porphyrins. In the case of the Zn(II) diad 10Zn , transient nanosecond-laser spectroscopy showed that no radical−ion intermediate was detected (Figure ) and the lifetime of the excited triplet state of 10Zn ( 3 ( 10Zn ) * ) became shorter than that of 1Zn : τ t = 3.0 μs ( 10Zn ) and τ 0 t = 7.9 μs ( 1Zn ) in MeCN and τ t = 3.5 μs ( 10Zn ) and τ 0 t = 4.4 μs ( 1Zn ) in MeOH.…”
Section: Resultsmentioning
confidence: 83%
“…Fluorescence data for N- alkylporphyrins and metalloporphyrins are summarized in Table . N- Alkylporphyrins have unique fluorescence properties compared with non- N- substituted porphyrins: red shifts in the emission maxima, a considerable decrease in the quantum yield, and larger Stokes' shifts between the Q x (0,0) absorption and Q x (0,0) fluorescence peaks. , This fact can be explained by the noncoplanarity of the porphyrin plane. Conformationally distorted non- N- substituted porphyrins, such as dodecasubstituted porphyrins, have shown considerable decrease in the fluorescence quantum yield .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations